The International Selection Decision: A Study of Some Dimensions of Managerial Behavior in the Selection Decision Process - Miller, Edwin L. (Academy of Management Journal, 1973)
This study is concerned with manager?s behavior within the international personnel selection decision process. Managers play an active role in the process, and their behavior is influenced by their perception of the job environment, the candidate?s qualifications, and the availability of persons qualified to fill the fob.